Wheat resistance to Fusarium head blight and possibilities of its improvement using molecular marker-assisted selection - Liaqat SHAH; Asif ALI; Yulei ZHU; Shengxing WANG; Hongqi SI; Chuanxi MA (Czech Journal of Genetics and Plant Breeding, 2017)
Wheat, one of the world's major crops, is seriously affected by fungal diseases, especially in regions with high moisture and moderately warm temperatures. This paper reviews various molecular and conventional techniques that are used to identify genotypes with resistance alleles associated with Fusarium head blight (FHB) diseases. Quantitative trait loci (QTL) type II, designated as Fhb1, are frequently applied in plant breeding, and the newly recognized genes related to resistance to this fungal disease give extra insights into marker-assisted selection (MAS). Molecular markers are robust tools that may be routinely used in MAS for the mapping of resistance genes in crop breeding. FHB resistance is polygenic, and different resistance genes could be conveyed into a single genotype by MAS, which might ensure greater resistance to FHB disease. In conclusion, different researchers have used various techniques to control FHB resistance, such as MAS, gene pyramiding (through backcross), and molecular markers (association with resistance QTLs or genes).